Benefits and Burdens of Using a SNP Array in Pregnancies at Increased Risk for the Common Aneuploidies. Issue 3 (March 2015) - Van Opstal, Diane; de Vries, Femke; Govaerts, Lutgarde; Boter, Marjan; Lont, Debora; van Veen, Stefanie; Joosten, Marieke; Diderich, Karin; Galjaard, Robert‐Jan; Srebniak, Malgorzata I.
<x xml:space="preserve">Abstract</x> Here we show the additional diagnostic value of SNP array as compared to rapid aneuploidy detection and karyotyping in 1330 pregnancies without ultrasound abnormalities. Our results show that in addition to the age or screening related aneuploidy risk, there is a risk of 1:148 for a (sub)microscopic abnormality associated with an early‐onset often severe disease, 1:222 for a submicroscopic aberration causing an early‐onset disease, 1:74 for carrying a susceptibility locus for a neurodevelopmental disorder, and 1:443 for a late‐onset disorder. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>